Perception of a Naturalistic Stressor Interacts with 5-HTTLPR/rs25531 Genotype and Gender to Impact Reward Responsiveness - Nikolova, Yuliya (S. Karger AG, 2011)
BACKGROUND: Stressful life experiences frequently precede the onset of major depression; however, the mechanisms that underlie this link are poorly understood. Importantly, some individuals are more susceptible to the depressogenic effects of stress than others. Carriers of the S or L(G) allele of the 5-HTTLPR/rs25531 polymorphisms (S’ participants) have been found to be more prone to developing depression under stress relative to L or L(A) homozygotes (L’ participants). Moreover, emerging evidence indicates that stress-induced anhedonia may be a mechanism underlying links between stress and depression. Given these findings, we hypothesized that exposure to a naturalistic stressor (school final examinations) would disrupt reward responsiveness (a key behavioral component of anhedonia), and that this effect would be strongest in S’ participants. METHODS: To objectively assess reward responsiveness, we administered a probabilistic reward task to 70 Bulgarian high school students over two sessions in the 6-month period preceding school finals. For each participant, the two sessions were designated as the ‘stress’ and ‘control’ conditions based on self-reported perceived stress. RESULTS: A genotype × condition interaction emerged in males, with S’ participants showing larger stress-related reduction in reward responsiveness relative to L’ participants. CONCLUSION: While in need of replication in a larger sample, our results indicate that stress associated with a real-life event is linked to reduced reward responsiveness, the susceptibility to which is modulated by 5-HTTLPR/rs25531 genotype. Although preliminary, these findings identify anhedonia as a promising mechanism linking 5-HTTLPR/rs25531 genotype and stress to depression.